Dylematy polityki rodzinnej - Kalinowska-Sufinowicz, Baha (Dillemas of Family Policy, 2009)
The main goal of the paper is to present problems of family policy. At the beginning definitions of family and next ideas and types of family policy were presented. Considering the possibilities of the state in the fields of improving the position of the family at various stages of its development the instruments of family policy were shown referring to the situation in Poland after the period of the economic transformation and the process of the accession to the European Union. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 130-137